DIGITAL TECHNOLOGIES IN VISUAL ARTS EDUCATION FOR GRADES 5–7 IN GENERAL SECONDARY SCHOOLS - Xamidova Dildora Muhiddin qizi (SCIENCE AND CULTURE: INNOVATIONS OF THE 21ST CENTURY, 2025)
Annotation: This article investigates the role of digital technologies in teaching visual arts to students in grades 5–7 in general secondary schools. It explores interactive lesson strategies, multimedia applications, and digital drawing tools that promote creativity, artistic skills, and visual literacy. The study emphasizes how technology enhances engagement, supports individualized learning, and encourages collaborative art projects.